Cell apoptosis and regeneration of hepatocellular carcinoma after transarterial chemoembolization - Li, Zhen (World J Gastroenterol, 2004)
AIM: To evaluate whether cell apoptosis and regeneration were existed in normal liver cells adjacent to carcinoma after transarterial chemoembolization (TACE). METHODS: Fifty rabbits with hepatic carcinoma were divided into 5 groups at random: group A (control group), groups B and C (TACE treatment groups), groups D and E (partial hepatectomy groups). There were 10 rabbits in each group. Rabbits in groups B-E were treated by transarterial chemoembolization (TACE) and partial hepatectomy (PH) respectively. The changes of S-phase cell fraction (SPF), proliferation index (PI) and cell apoptosis in the normal liver tissue were determined with flow cytometry (FCM) after operations on the first and third days. We determined the mitosis index (MI) with histo-pathological method and the apoptosis index (AI) with TUNEL method at the same time. RESULTS: Twenty-four hours after operations, compared with control group, the rabbits in TACE group had much higher index of SPF, PI and MI (MI: t = 4.89, P < 0.001; SPF: t = 5.27, P < 0.001; PI: t = 4.87, P < 0.001). Moreover, the proliferation of liver cells in TACE group was much weaker than that of the cells treated by partial hepatectomy, and the differences were significant (MI: t = 7.02, P < 0.001; SPF: t = 4.06, P < 0.001; PI: t = 2.70, P < 0.05). Seventy-two h after operations, FCM showed a small sub-G1 peak in TACE group and PH group, compared with the control group, but there was no difference between them (t = 0.41, P > 0.05). TACE showed that AI in the treated rabbits was higher than that in control group (t = 3.07, P < 0.05), and there were no differences between TACE group and PH group, either (t = 0.93, P > 0.05). CONCLUSION: Cell apoptosis and regeneration exist in rabbit liver tissues after TACE in some degree, which may be associated with the selective embolization of iodised oil, chemotherapeutic drug and free radical damage.